THE EXISTENCE OF ILLOCUTIONARY ACTS AND ITS TYPES USED IN “SEARCHING” MOVIE - Maharani, Puja; Mubarak, Zia Hisni (eScience Humanity Journal, 2023)
Communication is very important in human relations. Fluency and understanding of communication can launch things to be achieved for a speaker. This research aimed to analyze the existence of illocutionary acts and the types of illocutionary acts used in a movie (Searle & Vanderveken, 1985). This research used a 2018 movie entitled Searching as a data source. This film told about the efforts of a father to find his missing daughter in various ways. The Searching movie taken as the data source because the movie is unique and different from the others. This research used qualitative descriptive method because the analysis carried out will be explained in a narrative text that contains words. The collecting data method in this research used non-participant technique. The approach used in this study is a pragmatic approach. The results found from this study indicate the existences of using illocutionary acts in the data source and the use of its types in the form of declarative, expressive, commissive, directive, and representative. The speech acts theory of illocutionary acts were implemented in every conversation found in the movie of “Searching”.